Cultural variability among nine isolates of Urocystis agropyri on wheat - Karwasra, SS; Beniwal, MS; Chhabra, ML (Bangladesh Journal of Agricultural Research, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Four temperatures and five different media were tested for cultural variability of nine geographical isolates of Urocystis agropyri (Preuss.) Schroet causing flag smut of wheat. Urocystis agropyri is extremely slow growing pathogen and each isolate responded differently at different temperatures. All the isolates/ collections grew well at 20Â°C after 45, 60, and 70 days after incubation. Ambala isolate was fast growing. PDA medium was found to be most suitable for the growth of all the nine isolates/collections. The average mycelial growth was also maximum on Potato Dextrose Agar Medium followed by Corn Meal Dextrose Agar, Oat Meal Dextrose Agar, Grain Meal Dextrose Agar and minimum on Wheat Meal Dextrose Agar. Key Words: Variability, media, isolates, wheat. doi:10.3329/bjar.v33i3.1593 Bangladesh J. Agril. Res. 33(3) : 347-351, September 2008